Harmonisasi Asas Legalitas Formal dengan Pengakuan Hukum yang Hidup di Masyarakat (Living Law) dalam Kitab Undang-Undang Hukum Pidana Nasional - Icha Sri Herlina (Jurnal Hukum Lex Generalis, 2025)
The enactment of the National Criminal Code, which recognizes 'living law' in Article 2, creates a direct normative antinomy with the Principle of Legality stipulated in Article 1. This conflict fundamentally threatens the principle of legal certainty for citizens and jeopardizes the right to a fair trial for the accused. The need to find a solution is particularly urgent given that the National Criminal Code will come into effect in January 2026, which could potentially create legal chaos in the absence of clear guidelines. Therefore, this research aims to analyze this problem and formulate a harmonization model that can bridge the two conflicting concepts. To achieve this objective, a normative juridical research method is employed, utilizing statutory and conceptual approaches to analyze relevant legal norms and doctrines. This research finds that the recognition of living law in the National Criminal Code creates a fundamental conflict with the Principle of Legality, risking the erosion of legal certainty and the violation of human rights. However, harmonization is achievable through a mutually reinforcing three-pillar model: systematic interpretation by judges, the application of strict material criteria in accordance with the law, and the establishment of implementing regulations to ensure procedural certainty. Therefore, the successful implementation of this norm depends entirely on the synergy of these three pillars to realize the ideal of legal pluralism without sacrificing the foundations of the modern rule of law.